Removal of metal ions from aqueous solution using trioctyl phosphine oxide-containing mixed solvents in conjunction with a fibre-supported solid membrane - Gaikwad, Abaji G. (Adsorption Science & Technology, 2011)
A novel method has been developed for the removal of mercury, arsenic and tin ions using a fibre-supported solid membrane placed between the source phase and the receiving phase which contained trioctyl phosphine oxide (TOPO) in a mixed solvent. The fibre-supported solid membrane was prepared by the esterification of cellulose fibre with tartaric acid at 120 degrees C. The experimental variables explored were the initial concentration of the metal ion (10(-2) to 10(-4) M) in the source phase, the type of mixed solvent employed [containing TOPO, TOPO + acetone, TOPO + tetrahydrofuran, TOPO + 1,4-dioxane, TOPO + methanol, TOPO + ethanol or TOPO + 2-propanol (20-80% v/v)], the concentration of HCl (0.25-1 M) in the receiving phase and the stirring speed (50-130 rpm) of the bulk source and the receiving phase. The efficiency of the organic solvent in the mixed solvent followed the order: TOPO + tetrahydrofuran > TOPO + 1,4-dioxane > TOPO + acetone > TOPO + 2-propanol > TOPO + ethanol > TOPO + methanol > TOPO. The separation of the metal ions was discussed.